2022
DOI: 10.3390/ijms23031527
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effect of an O-2-Substituted (1-3)-β-D-Glucan Produced by Pediococcus parvulus 2.6 in a Caco-2 PMA-THP-1 Co-Culture Model

Abstract: Bacterial β-glucans are exopolysaccharides (EPSs), which can protect bacteria or cooperate in biofilm formation or in bacterial cell adhesion. Pediococcus parvulus 2.6 is a lactic acid bacterium that produces an O-2-substituted (1-3)-β-D-glucan. The structural similarity of this EPS to active compounds such as laminarin, together with its ability to modulate the immune system and to adhere in vitro to human enterocytes, led us to investigate, in comparison with laminarin, its potential as an immunomodulator of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“…Huanghuang Dai et al [3], found a positive correlation between the addition of glucosylceramide and the induction of changes in the metabolism of Blautia coccoides, which leads to an increase in the number of Gram-positive bacteria in an intestine-simulating environment by endowing tolerance to deoxycholic acid. At the same time, the findings reported by Notararigo et al [4], clearly confirmed the immunomodulation of O-2-substituted-(1-3)-β-D-glucans in an in vitro model of intestinal gut mucosa after the stimulation of PMA-THP-1 cells with E. coli LPS, which triggered cellular response mechanisms. Hence, O-2-substituted-(1-3)-β-D-glucans is able to ameliorate immune system response in healthy individuals, as well as in individuals with some chronic inflammatory states.…”
supporting
confidence: 74%
“…Huanghuang Dai et al [3], found a positive correlation between the addition of glucosylceramide and the induction of changes in the metabolism of Blautia coccoides, which leads to an increase in the number of Gram-positive bacteria in an intestine-simulating environment by endowing tolerance to deoxycholic acid. At the same time, the findings reported by Notararigo et al [4], clearly confirmed the immunomodulation of O-2-substituted-(1-3)-β-D-glucans in an in vitro model of intestinal gut mucosa after the stimulation of PMA-THP-1 cells with E. coli LPS, which triggered cellular response mechanisms. Hence, O-2-substituted-(1-3)-β-D-glucans is able to ameliorate immune system response in healthy individuals, as well as in individuals with some chronic inflammatory states.…”
supporting
confidence: 74%
“…IFN-γ priming of Caco-2 cells together with the stimulation of differentiated THP-1 cells by LPS and IFN-γ, induced an inflammation-like response in their diseased intestine model, evident by intestinal barrier disruption and pro-inflammatory cytokine release. Based on this model of Kämpfer, co-culture models with differentiated Caco-2 cells and PMA-differentiated THP-1 cells in the presence of inflammatory stimulators (e.g., LPS with/without IFN-γ) have been used to evaluate the potential immunomodulatory and anti-inflammatory effects of phytochemicals [ 43 , 72 , 73 ], marine natural products [ 74 , 75 , 76 ], bacterial β-glucans [ 77 ], siRNA-based nanomedicine [ 42 ], bovine milk-derived extracellular vesicles [ 78 ], and probiotic bacteria [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…regulated intestinal operational physiological function by enhancing tight junctions and inhibiting inflammation of the intestines . Other immune cells such as DC cells, autologous T-cells, the human monocytes THP-1 cell line, the human histiocytic lymphoma U937 cell line, peripheral mononuclear cells (PBMCs), B-cells and so on have also been used to elucidate the anti-inflammatory abilities of Sulfoquinovosylmonoacylglycerols (derived from brown alga Turbinaria ornate ), resistant starches, Cudrania atrigelate fruits vinegar, phycocyanin and Ganoderma atrum polysaccharides. , …”
Section: Ive Systems In Functional Food Evaluationmentioning
confidence: 99%